Efektifitas Model Pembelajaran Pada Kelompok Belajar - Wathon, A (MASALIQ, 2025)
This study aims to analyze the effectiveness of the learning model in reading learning groups at Kindergarten (TK). The background of this research stems from the challenges faced by educators in improving early childhood reading skills. The method used in this research is a qualitative approach with in-depth interviews, observation, and documentation techniques. Data were collected from educators, students, and parents to obtain a comprehensive understanding of the application of the reading learning model used in the classroom. The results of the study indicate that the learning model, which uses a phonemic approach and is based on play, is very effective in enhancing children's interest and reading abilities. The children showed significant improvement in recognizing letters, sounds, and reading simple words after this method was implemented. Additionally, the active role of parents in supporting reading activities at home also contributed to the success of the learning process. The conclusion of this study is that the reading learning model based on play and the phonemic approach is highly effective in improving early childhood reading skills and can serve as a good alternative for implementation in early childhood education institutions. This study also recommends the need for training for educators to better apply appropriate methods according to the characteristics of the students.